1975
DOI: 10.1113/jphysiol.1975.sp010796
|View full text |Cite
|
Sign up to set email alerts
|

Excitation and contraction in bovine tracheal smooth muscle.

Abstract: SUMMARY1. The smooth muscle layer of the bovine trachea was studied in vitro with the micro-electrode and sucrose-gap techniques. The membrane potential was stable at -47-6 + 0-98 (S.E. of mean) mV, and there was no spontaneous electrical or mechanical activity.2. The cell membrane had strong rectifying properties, making it impossible to elicit action potentials by electrical stimulation in normal Krebs solution. The rectification was abolished by TEA (30 mmol/l), which depolarized the membrane and produced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
94
0
2

Year Published

1979
1979
1990
1990

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(106 citation statements)
references
References 31 publications
10
94
0
2
Order By: Relevance
“…Further, it is also conceivable that spontaneous contractions are artifactual due to the mediators released from the tissues by trauma during the preparative procedures. In accord with this, oscillations in membrane potential and subsequent spontaneous contractions have been observed in response to histamine (Kirkpatrick 1975) acetylcholine (Cameron & Kirkpatrick, 1977), 5-hydroxytryptamine (Coburn & Yamaguchi, 1977) or after prolonged treatment with indomethacin (Ito & Tajima, 1981b) in bovine or dog trachea. In the present experiments FPL 55712, indomethacin or atropine suppressed the slow waves and spontaneous contractions.…”
Section: Electrical Properties Ofthe Smooth Muscle Cells Of Human Bromentioning
confidence: 58%
“…Further, it is also conceivable that spontaneous contractions are artifactual due to the mediators released from the tissues by trauma during the preparative procedures. In accord with this, oscillations in membrane potential and subsequent spontaneous contractions have been observed in response to histamine (Kirkpatrick 1975) acetylcholine (Cameron & Kirkpatrick, 1977), 5-hydroxytryptamine (Coburn & Yamaguchi, 1977) or after prolonged treatment with indomethacin (Ito & Tajima, 1981b) in bovine or dog trachea. In the present experiments FPL 55712, indomethacin or atropine suppressed the slow waves and spontaneous contractions.…”
Section: Electrical Properties Ofthe Smooth Muscle Cells Of Human Bromentioning
confidence: 58%
“…Direct evidence that KClpromoted spasm is potential-dependent comes from experiments where current pulses which return the membrane potential towards normal also suppress the spasm (Coburn & Yamaguchi, 1977). Dependence of KCl-induced spasm on extracellular Ca2+ has been demonstrated in the trachealis of the ox (Kirkpatrick, 1975) and the guinea-pig (Creese & Denborough, 1981). As yet, however, there has been no direct demonstration in trachealis of K+-promoted cellular influx of Ca2+* The present study comprises an analysis of the spasmogenic action of KCl in guinea-pig trachealis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the rabbit airway, the potassium (128 mm K)-and histamine (10pM)-induced contractions in the trachea are much smaller than the acetylcholine (ACh, 10 M)-induced contraction, but in the third branch of the right middle bronchial tree, these same three stimulants generate much the same amplitude of contraction and, moreover, the amplitude of the ACh-induced contraction is larger than that observed in the trachea (Fujiwara et al, 1988). In the guinea-pig, dog, bovine and rabbit tracheal and bronchial tissues, histamine produces contraction by stimulation of the Hl-receptor, though H2-receptors are also present (Chand & Eyre, 1975;Kirkpatrick, 1975;Kotlikoff et al, 1987). Ito & Tajima (1982) demonstrated that in the dog trachea, isoprenaline produces hyperpolarization of the membrane, reduces the resting tone and relaxes tissues precontracted by ACh.…”
Section: Introductionmentioning
confidence: 99%